2011
DOI: 10.1177/0020764011430037
|View full text |Cite
|
Sign up to set email alerts
|

Depression and the medicalization of sadness: Conceptualization and recommended help-seeking

Abstract: Background:Critiques of the validity of the DSM diagnostic criteria for depressive disorder argue that it fails to differentiate between abnormal sadness due to internal dysfunction or depression (sadness without an identifiable cause), and normal sadness (sadness with a clear cause).Aims and Methods:A population survey was undertaken in adult education centres in Spain aiming to explore beliefs about depression and normal sadness. Two hypothetical case vignettes portrayed individuals experiencing deep sadness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…In our study, based on the intensity perceived only, irrespective of the semantic considerations of emotion, we separated the two classes of sad-like music. Our results were supported by a clinical consideration that depression was a severe form or medicalization label of sadness 47. Moreover, in music, it has been consistently found that sad music induces negative, positive, and mixed emotions,44,48,49 and music-evoked sadness is composed of grief, melancholia, and sweet sorrow 50.…”
Section: Discussionsupporting
confidence: 84%
“…In our study, based on the intensity perceived only, irrespective of the semantic considerations of emotion, we separated the two classes of sad-like music. Our results were supported by a clinical consideration that depression was a severe form or medicalization label of sadness 47. Moreover, in music, it has been consistently found that sad music induces negative, positive, and mixed emotions,44,48,49 and music-evoked sadness is composed of grief, melancholia, and sweet sorrow 50.…”
Section: Discussionsupporting
confidence: 84%
“…The same pattern was found with other emotional variables such as separation anxiety ( Boelen, 2013 ) or experiential avoidance ( Boelen et al, 2010 ). These results suggest that CG is associated with a general psychopathological profile of more powerful symptoms, that could, for example, be related to the high rates of medication in this population ( Durà-Vilà et al, 2013 ; Bandini, 2015 ; García and Landa, 2015 ).…”
Section: Introductionmentioning
confidence: 91%
“…Korean and Russian participants endorsed the view of depression as a personal weakness more than participants in the USA. In a similar way, Dura Villa et al 43 observed that Spaniards were unlikely to view symptoms of depression triggered by negative life events, such as the illness of a family member, as pathological.…”
Section: Normative and Pathological Scriptsmentioning
confidence: 88%